Tracking the Trajectories of Genni Gunn’s Writing - Saidero, Deborah (Italian Canadiana)

(untitled) (Iter Press, 2023)
This article examines Genni Gunn’s writing in light of her childhood immigration experience and contends that, despite the crypto-ethnic approach she has adopted vis-à-vis her Italian-Canadian heritage, migration figures prominently in both her fictional and personal works, which bear traces of her autobiographical vicissitudes and reflect her own process of coming to terms with trauma. Indeed, her novels, stories, poems, and travel accounts all develop along shared trajectories, which include not only the obsession with travel, movement, and memory, or the search for identity and interpersonal ties, but also the focus on loss, grief, and abandonment, which are typical psychopathologies of migration trauma. Ultimately, Gunn embraces creative writing as a site of healing from the loss and pain endured as an effect of separation, abandonment, and migration, which are investigated beyond identification with a specific ethno-cultural group to encompass universal human experiences of trauma.